A new method for the determination of combustible sulphur in coal - (:unkn) unknown (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY, 1995)
A new method for the determination of combustible sulphur in coal is introduced. This method involves calculation of combustible,sulphur as the difference between total sulphur in coal and total sulphur in coal ash. Comparison of results with combustible sulphur dereminations via the calorimeter bomb method reveals that the proposed method inherently accounts for the interactions between coal ash and sulphur dioxide emissions during combustion. Hence, this method is expected to yield better estimates of sulphur dioxide emissions from fixed or fluidized bed combustors, especially for coals with high total sulphur and high ash contents.
Keywords: SULFUR RETENTION; ASH